The genome of the cauliflower coral pocillopora verrucosa - Buitrago-López, Carol; Mariappan, Kiruthiga G.; Cárdenas, Anny; Gegner, Hagen M.; Voolstra, Christian (Genome biology and evolution, 2020)
Climate change and ocean warming threaten the persistence of corals worldwide. Genomic resources are critical to study the evolutionary trajectory, adaptive potential, and genetic distinctiveness of coral species. Here, we provide a reference genome of the cauliflower coral Pocillopora verrucosa, a broadly prevalent reef-building coral with important ecological roles in the maintenance of reefs across the Red Sea, the Indian Ocean, and the Pacific Ocean. The genome has an assembly size of 380,505,698 bp with a scaffold N50 of 333,696 bp and a contig N50 of 75,704 bp. The annotation of the assembled genome returned 27,439 gene models of which 89.88% have evidence of transcription from RNA-Seq data and 97.87% show homology to known genes. A high proportion of the genome (41.22%) comprised repetitive elements in comparison to other cnidarian genomes, in particular in relation to the small genome size of P. verrucosa.
Gesehen am 18.01.2021